WACC and a Generalized Tax Code - Sven Husmann; Lutz Kruschwitz; Andreas Löffler (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2001)
We extend the WACC approach to a tax system having a firm income tax and a personal income tax of the investor as well. We use an artificial tax system incorporating most of the G-7 national tax codes as for example the classical or the imputation systems.
Keywords: 330; Valuation; Tax; WACC